2018
DOI: 10.3892/mmr.2018.9616
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑495 targets Notch1 to prohibit cell proliferation and invasion in oral squamous cell carcinoma

Abstract: MicroRNAs (miRNAs) are associated with the initiation and progression of oral squamous cell carcinoma (OSCC) by regulating a variety of cancer-associated behaviors. Fully understanding the regulatory mechanism of miRNAs in the pathogenesis of OSCC may provide novel promising approaches for the identification of prognostic biomarkers and therapeutic targets for this particular malignancy. In the present study, reverse transcription-quantitative polymerase chain reaction analysis was performed to detect miRNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…For example, in endometrial cancer (EC), miR-495 was downregulated in tumor tissues, and overexpression of miR-495 markedly inhibited tumor cell proliferation and promoted cell apoptosis via targeting PIK3R1 [28]. In oral squamous cell carcinoma (OSCC), miR-495 was also reported to play an antitumor effect through regulating OSCC cell growth and metastasis [29]. In healthy cells, miR-495 was also reported to participate in a variety of developmental, apoptotic, immune and inflammatory mechanisms [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in endometrial cancer (EC), miR-495 was downregulated in tumor tissues, and overexpression of miR-495 markedly inhibited tumor cell proliferation and promoted cell apoptosis via targeting PIK3R1 [28]. In oral squamous cell carcinoma (OSCC), miR-495 was also reported to play an antitumor effect through regulating OSCC cell growth and metastasis [29]. In healthy cells, miR-495 was also reported to participate in a variety of developmental, apoptotic, immune and inflammatory mechanisms [30].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, overexpression of miR-495 inhibited the proliferation, migration, and invasion while stimulating the apoptosis of CSCs in OSCC by downregulating its target HOXC6 gene. Similarly, the overexpression of miR-495 inhibits OSCC cell proliferation and invasion through its suppression in Notch1 target gene in vitro [10]. One previous study suggested that 14q32.31 miRNAs, including miR-495, play important roles in the inhibition of cell proliferation, invasion, and migration in metastatic prostate cancer, where miR-495 could decrease cells in proliferative S phase while increase cells in the G1 phase [37].…”
Section: Discussionmentioning
confidence: 96%
“…A recent study suggests that miR-495 may serve as a tumor suppressor by inhibiting the migration and invasion of gastric cancer cells [9]. In addition, restored miR-495 expression can restrict cell proliferation and invasion in OSCC cells in vitro by repressing its target gene Notch1 [10]. The HOX gene family consists of 39 genes that organize into 4 chromosomal loci, which has been reported to play a significant role in organogenesis via regulation of proliferation, differentiation, survival, migration, and invasion [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al has found that miR-495 restricts the proliferation and invasion of OSCC cells by directly targeting Notch1. Notch1 knockdown shows an inhibitory effect similar to that induced by miR-495 overexpression in OSCC cells [46]. Cyclin-dependent kinase (CDK) and cyclin-dependent kinase inhibitor (CDKI) can directly control the cell cycle.…”
Section: Discussionmentioning
confidence: 99%